Petrology, Geochemistry, and Peak Pressure-Temperature Metamorphism of Pinoh Metamorphic Rocks in The Schwaner Mountains, Indonesia - Nugroho Imam Setiawan; Agung Harijoko; Rahmadi Hidayat; I Gde Sukadana; Frederikus Dian Indrastomo; Isyqi (Indonesian Journal on Geoscience, 2026)
The Pinoh Metamorphic Rocks in the Schwaner Mountains predominantly underwent contact metamorphism near a granitoid body, oriented E–W and NW–SE. The whole-rock geochemical analyses indicate that these metapelites are characterized by high Al₂O₃ (16.6–22.0 wt.%), moderate SiO₂ (60.0–67.7 wt.%), low CaO and Na₂O, and enrichment in large-ion lithophile elements relative to high field strength elements. Trace-element and REE patterns normalized to upper continental crust show LREE enrichment, negative Sr anomalies, and variable Zr contents, suggesting significant sedimentary recycling. Chemical weathering indices (CIA = 79–89; CIW = 89–99) and low ICV values (0.58–0.75) indicate compositionally mature pelitic to semipelitic protoliths. Provenance discrimination diagrams suggest derivation mainly from intermediate to felsic-igneous sources, with minor mafic contributions, deposited in an active continental margin to continental arc setting. Integrated petrographic, microstructural, mineral-chemical, thermobarometric, and phase equilibria analyses of samples from the Nanga Pinoh and Nanga Semalam areas reveal two main metamorphic events (M1 and M2). The M1 event formed the primary S1 foliation, whereas the M2 event is marked by the growth of andalusite porphyroblasts and the occurrence of spotted biotite. Garnet locally nucleated during late M1, but was chemically re-equilibrated during M2. Peak metamorphic conditions of the garnet–andalusite–biotite schist, estimated using garnet–biotite–andalusite–quartz (GBAQ) geothermobarometry and pseudosection modeling, yield P–T conditions of 525–586° C at 2.0–3.8 kbar, consistent with low-pressure, high-temperature Buchan-type contact metamorphism related to Cretaceous granitoid magmatism in The Schwaner Mountains.